114 FALLS AND SYNCOPE GUIDELINES APPLIED TO EMERGENCY DEPARTMENT ATTENDEES—HOW DO WE PERFORM?. (18th November 2021) - Merron, G; Lyons, C; Dockery, F
Abstract: Background: Falls and syncope are one of the most common presentations to emergency departments amongst older people. European Society of Cardiology (ESC) guidelines describe investigation of suspected syncope to assist care. Methods: Following a previous audit we delivered an education program to Emergency Department (ED) staff, on assessment of fallers and syncope. This was a repeat cycle audit on consecutive patients aged who presented with a fall/faint/collapse/blackout/syncope, to assess impact of education sessions. We also conducted a survey of n = 23 ED staff members, on role of orthostatic blood pressures and ECGs in falls assessments. Results: Of 80 consecutive attendees with a fall, n = 41 (51%) had possible syncope as documented in the history. ECG was done within the ED in 88% vs. 51% on baseline audit however only 14% (11/80) had lying and standing blood pressure checked vs. 15% on baseline audit. This is despite our survey showing that 17/23 (74%) of ED staff felt that orthostatic BP checks were essential in all fallers, and 44% stating they measure it themselves. Brain imaging was conducted in 44% vs. 40% in baseline audit, rationale for which was unclear in some. 31% (n = 25) were admitted compared to 42% previously. Of the n = 23 admitted, 24% (n = 6) had telemetry or Holter monitor, 20% had an echocardiogram. Conclusion: Despite an education program on assessment of older fallers, embedding it to alter practice is challenging. While the education program resulted in some improvements, it supports a dedicated team for assessing fallers in the ED. Given the low rate of further investigations into causes for those admitted, a rapid access out patient pathway is warranted. Brain imaging is carried out relatively frequently though we cannot conclude on appropriateness in this limited audit.